Beneficial effect of fish oil on blood viscosity in peripheral vascular disease. Issue 6417 (25th February 1984) - Woodcock, B E; Smith, E; Lambert, W H; Jones, W M; Galloway, J H; Greaves, M; Preston, F E
Abstract : Reports suggest that the low incidence of ischaemic heart disease in Greenlandic Eskimos is related to the effect of a diet rich in eicosapentaenoic acid on platelet reactivity and plasma lipid concentrations. A double blind randomised investigation was therefore conducted of the effects on blood viscosity of dietary supplementation with an oil rich in this fatty acid (1.8 g/day, given as fish oil) and an eicosapentaenoic acid poor oil (as corn/olive oil) in patients with peripheral arterial disease. A statistically significant reduction in whole blood viscosity was observed at seven weeks in those patients receiving the eicosapentaenoic acid rich oil. No changes in plasma viscosity, haemoglobin concentration, packed cell volume, or platelet count were seen. A significant fall in plasma triglyceride concentration was also noted only in the patients receiving oil rich in eicosapentaenoic acid; plasma concentrations of cholesterol and high density lipoprotein cholesterol were unchanged. It is concluded that rheological changes that result from a diet rich in eicosapentaenoic acid may contribute to the suggested protective effects of such a diet against arterial disease and that such changes are of potential therapeutic importance in established arterial disease.